Unlimited Power : The New Science of Personal Achievement - Robbins, Anthony (New York Fireside Rockefeller Center, 1997)
This self-help guide shows the reader step-by-step how to perform at their peak while gaining emotional and financial freedom, attaining leadership and self-confidence, and winning the confidence of others. It should enable the reader to gain the knowledge and courage to remake themselves.
Keywords: Success--Psychological aspects -- Neurolinguistic programming -- Success